Penyelesaian Perjanjian Kredit Dalam Hal Debitur Telah Meninggal Dunia Tanpa Kepemilikan Asuransi (Studi di PT. Bank Nagari Cabang Utama) - Danovand, Calvin; Azheri, Busyra; Adelina Mannas, Yussy (UNES Law Review, 2023)
Credit agreements are provisions that have legal certainty and apply as law to the parties to the agreement. In accordance with Article 1338 of the Civil Code paragraph (1) states that, "Any agreement made by the parties concerned constitutes a binding law between the two parties." So that in every credit agreement between the creditor and the debtor gives rise to a binding force between the debtor and the creditor, the settlement must be obedient and in accordance with the grace period that has been determined by both parties. Based on the background above, the problems to be studied are: 1) How to resolve the credit agreement in the event that the debtor has died without insurance ownership in PT. Bank Nagari West Sumatra Region? 2) How to carry out the responsibility of the heirs who receive inheritance on the debts of the heirs in PT. Bank Nagari West Sumatra Region? To solve the problem, an empirical juridical approach is used with the main data being primary data in the form of primary, secondary and tertiary legal materials. The results of the study and discussion that the Settlement of credit agreements for debtors has died without ownership of life insurance in Nagari Bank. Based on the results of the study, the following data can be obtained; 1) Guided by the legal provisions of Article 1381 of the Civil Code, steps taken after the event of the deceased debtor's situation, namely: payment, cash payment offer followed by storage or custody (consignation), debt renewal (novation), , debt encounters (compensation), mixing debts (confucion), debt relief, destruction of objects / goods that are the object of the agreement, void terms in each agreement (void / cancel), the enactment of a condition is void, and because of the expiration of time (expiration). This effort is made after the situation of the debtor has died. In addition, ways are taken through banking administration, non-litigation and litigation methods 2) The mechanism for the Implementation of Heir Responsibilities for the Debts of the Deceased Heir is by deliberation between the Credit Rescue Division and the Credit Officer with the Heirs of the debtor concerned. It aims to seek agreement on the payment of the remaining outstanding debtor credit to be settled and to look back at how the debtor's business was abandoned as well as what the condition of the collateral was collateralized to the bank. At that time, the bank assesses the ability to repay as well as the character of the customer itself. Research Methods. In conclusion, Bank Nagari was negotiate with the debtor's heirs who do not have the ability to pay their credit. Bank Nagari proposed the sale of the credit collateral, and found a third party who wanted to buy and sell the collateral to cover the credit.. Advice, maintain communication more intensely to safeguard the rights of both parties.